Effectiveness of Use of D-Kay Cleaner in The Wooden Furnitures Industry in Padang City in 2023 - Putri, Salsabila Refinda; Mahaza; Suksmerri; Desman, Akhirul; Darwel; Onasis, Aidil; Nellianis (proceedinginternational, 2024)
The main problem of workers' health is respiratory disorders, which is certainly related to the air quality in wooden furniture. The wood processing industry is a very rapidly growing industry and is widely absorbed by the polywood, sawmill, and furniture industries. As well as potentially causing air pollution in the workplace in the form of wood dust. Because about 10 to 13% of sawn wood will be sawdust. Occupational respiratory diseases, according to the results of The Surveillance of Work Associated and Occupational Respiratory Disease (SWORD) research conducted in the UK, found 3300 new cases of occupational lung disease. The purpose of this study is to determine the usefulness of products and the effectiveness of innovative D-Kay Cleaner products in the wood furniture industry, so that they can be utilized by the wider community. D-Kay Cleaner will be an easy and acceptable medium for the public in carrying out respiratory prevention. In the D-Kay Cleaner testing process, tool manufacturing was carried out starting from oil bottle experiments, welding boxes, and used. box. The innovation of the D-Kay Cleaner tool uses the principle of a vacuum cleaner. But the difference is that the tools and materials for making it are more economical, and use a layer of mask as a filter. Therefore, it is necessary to develop d-kay cleaners on the scale of wood furniture workers to reduce the amount of wood dust produced, and can reduce the negative impact of respiratory disorders.